2022
DOI: 10.1021/acs.est.2c04124
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Asymmetry of the Active Layer in Pursuit of Nanofiltration Selectivity via Differentiating Interfacial Reactions of Piperazine

Abstract: Nanofiltration (NF), highly prospective for drinking water treatment, faces a challenge in simultaneously removing emerging contaminants while maintaining mineral salts, particularly divalent cations. To overcome this challenge, NF membranes possessing small pores concomitant with highly negatively charged surfaces were synthesized via a two-step fabrication strategy. The key is to generate a polyamide active layer having a loose and carboxyl group-abundant segment on top and a dense barrier segment underneath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…We further found that TFC-l-A with inhibited polyamide intrusion exhibited higher rejection of emerging contaminant, due to the normalized pores and reduced defects in the selective layer. , Since the inhibition of intrusion theoretically affected only the permeance of the selective layer, this might be caused by the aminated substrate. Besides the reactivity, the amino groups could promote the formation of a more homogeneous reaction interface and thus reduced defects in the selective layer.…”
Section: Implicationmentioning
confidence: 70%
See 2 more Smart Citations
“…We further found that TFC-l-A with inhibited polyamide intrusion exhibited higher rejection of emerging contaminant, due to the normalized pores and reduced defects in the selective layer. , Since the inhibition of intrusion theoretically affected only the permeance of the selective layer, this might be caused by the aminated substrate. Besides the reactivity, the amino groups could promote the formation of a more homogeneous reaction interface and thus reduced defects in the selective layer.…”
Section: Implicationmentioning
confidence: 70%
“…NF membranes with enhanced water permeance and mono/ divalent salt selectivity could lead to the dramatic increase in process efficiency. 3,51 Moreover, membranes with uniform pore size and surface charge distribution show many potential applications, such as the removal of highly toxic trace solutes (e.g., emerging contaminants) from potable water. 52, 53 Figure 5c shows that TFC-l-A exhibited higher rejection of tetracycline (about 98%) compared to the control TFC-l-O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all membranes, the rejection of SO 4 2– was much higher than that of Cl – , which is a characteristic of negatively charged membranes, relatively regardless of the negative charge density. The higher rejections of Mg 2+ and Ca 2+ than Na + even when the membrane surface negative charge density was enhanced, different from the rejection behavior for single salt solutions, was due to the fact that Mg 2+ and Ca 2+ have stronger steric hindrance and dielectric effects compared with Na + and higher hydration energy so that they are not easy to dehydrate to enter membrane pores, especially when the membrane pore sizes are relatively small. , …”
Section: Resultsmentioning
confidence: 99%
“…The probable swelling and deformation of polyelectrolyte layers induced by high salinity and pressure conditions are obstacles which need to be solved for the practical applications of PEM membranes. , Large-scale fabrication of these membranes also remains a challenge. Besides the commonly used modification methods and polymer-based novel chemistry of selective layers elaborated in detail in this review, other delicate strategies (e.g., capillary-assisted IP and amine modification , ) to regulate the formation of PA membranes and exploitation of two-dimensional nanomaterials (e.g., graphene oxide, molybdenum disulfide, MXene, , etc.) as building blocks of selective layers have attracted growing research interests in recent years.…”
Section: Concluding Remarks and Research Outlookmentioning
confidence: 99%